2004
DOI: 10.1111/j.1754-7121.2004.tb01182.x
|View full text |Cite
|
Sign up to set email alerts
|

An auditor's best friend? Standing committees on public accounts

Abstract: This article looks at public accounts committees (PACS) in Canadian legislatures and their relationship with legislative auditors. In most jurisdictions, there is a close relationship between the two, as PACS base their agenda on auditors' reports and interact significantly with auditors. The chief role of the committees is to provide a unique and important public forum for the further exploration of issues identified by auditors. Their effectiveness is thus not necessarily in their written reports as much as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
1
12
0
2
Order By: Relevance
“…D'autre part, l'invitée surprise de la Loi fédérale sur la responsabilité 4 -la soumission des organisations privées recevant des subsides fédéraux aux juridictions du BVG -a l'apparence d'un cadeau empoisonné pour le BVG. À ressources égales, soit il effectue ce travail au risque d'avoir moins de ressources à investir dans la fourniture de munitions à l'opposition et aux médias pour attaquer la majorité (Malloy, 2004), soit il ne l'effectue pas -ce qui est l'option défendue actuellement par le BVG (interview avec un cadre du BVG, 2009). Si toutefois un scandale éclatait impliquant une organisation privée soumise théoriquement au contrôle du BVG, celui-ci aurait du mal a éviter d'endosser la responsabilité que le gouvernement n'hésiterait pas à lui faire porter.…”
Section: Resultsunclassified
“…D'autre part, l'invitée surprise de la Loi fédérale sur la responsabilité 4 -la soumission des organisations privées recevant des subsides fédéraux aux juridictions du BVG -a l'apparence d'un cadeau empoisonné pour le BVG. À ressources égales, soit il effectue ce travail au risque d'avoir moins de ressources à investir dans la fourniture de munitions à l'opposition et aux médias pour attaquer la majorité (Malloy, 2004), soit il ne l'effectue pas -ce qui est l'option défendue actuellement par le BVG (interview avec un cadre du BVG, 2009). Si toutefois un scandale éclatait impliquant une organisation privée soumise théoriquement au contrôle du BVG, celui-ci aurait du mal a éviter d'endosser la responsabilité que le gouvernement n'hésiterait pas à lui faire porter.…”
Section: Resultsunclassified
“…Plusieurs études confirment que les parlementaires sont des alliés sûrs des auditeurs législatifs pour améliorer la qualité de la reddition de comptes par les Administrations et aussi pour accroître les chances d'impact des auditeurs sur les Administrations au moyen des missions d'audit de performance (Brown, 2007 ;Malloy, 2004 ;Morin, 2008 ;Pollitt et autres, 1999 ;Roberts et Pollitt, 1994 ;Vanlandingham, 2006). Les études reconnaissent aussi la nécessité d'une véritable indépendance de fait et d'esprit des auditeurs législatifs à l'égard du pouvoir exécutif (Funnell, 1994 ;Morin, 2010 ;Norton et Smith, 2008 ;Wheat, 1991).…”
Section: Depuis Plus De Trente Ans Que Les Auditeurs Législatifs S'atunclassified
“…Pollitt et al (1999) noted that one of the key indicators of the impact of SAI is the degree of attention dedicated to their reports by parliamentarians. Malloy (2004) posits that Canadian public accounts committees formulate their work agenda based on the auditors' reports, and in return, committees provide auditors with a unique, important public forum that allows the study of questions identified in their reports in depth. Also in Canada, the research by Morin (2008) revealed strong correlations between the presence and intervention of Parliamentarians and a greater impact of performance audits conducted by the Quebec Auditor General.…”
Section: The Contemporary Court: 'Equidistant' Between Parliament Andmentioning
confidence: 99%